2009
DOI: 10.1007/s11738-009-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-mediated alleviation of cadmium toxicity in hemp plants in relation to cadmium uptake, photosynthesis, and antioxidant enzymes

Abstract: To assess the role of salicylic acid (SA) in alleviating cadmium (Cd) toxicity in hemp (Cannabis sativa L.) plants, the growth parameters, Cd accumulation, photosynthetic performance and activities of major antioxidant enzymes were investigated in hemp seedlings treated with 500 lM SA, under 0, 25, 50, and 100 mg Cd kg -1 sands (DW) conditions, respectively. Cd exposure resulted in a small reduction in biomass (12.0-26.9% for root, and 8.7-29.4% for shoot, respectively), indicating hemp plants have innate capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 66 publications
11
66
1
3
Order By: Relevance
“…Later, Belkadhi et al 2015 further reported that exogenous SA also protected phospholipids of L. usitatissimum by decreasing the percentages of monogalactosyldiacylglycerol, phosphatidylcholine, phosphatidylethanolamine and phosphatidylglycerol. The net result of exogenous SA application is the alleviation of Cd-induced root growth inhibition and overall attenuation of Cd toxicity-the latter of which has been reported for a variety of plants (e.g., V. faba (Popova et al 2009), O. sativa ), B. juncea (Ahmad et al 2011), G. max (Drazic andMihailovic 2005), L. usitatissimum (Belkhadi et al 2010), H. vulgare (Tamás et al 2015), Cannabis sativa (Shi et al 2009), Z. mays (Krantev et al 2008), T. aestivum (Agami and Mohamed 2013) and Pisum sativum (Popova et al 2009)). Salicylic acid is reported to reduce Cd toxicity to plants not only at the level of antioxidant defense but also by altering other mechanisms of Cd detoxification which are not yet well known (Gallego et al 2012).…”
Section: Salicylic Acid (Sa)mentioning
confidence: 88%
“…Later, Belkadhi et al 2015 further reported that exogenous SA also protected phospholipids of L. usitatissimum by decreasing the percentages of monogalactosyldiacylglycerol, phosphatidylcholine, phosphatidylethanolamine and phosphatidylglycerol. The net result of exogenous SA application is the alleviation of Cd-induced root growth inhibition and overall attenuation of Cd toxicity-the latter of which has been reported for a variety of plants (e.g., V. faba (Popova et al 2009), O. sativa ), B. juncea (Ahmad et al 2011), G. max (Drazic andMihailovic 2005), L. usitatissimum (Belkhadi et al 2010), H. vulgare (Tamás et al 2015), Cannabis sativa (Shi et al 2009), Z. mays (Krantev et al 2008), T. aestivum (Agami and Mohamed 2013) and Pisum sativum (Popova et al 2009)). Salicylic acid is reported to reduce Cd toxicity to plants not only at the level of antioxidant defense but also by altering other mechanisms of Cd detoxification which are not yet well known (Gallego et al 2012).…”
Section: Salicylic Acid (Sa)mentioning
confidence: 88%
“…Furthermore, SA application has been reported to alleviate the symptoms of Cd toxicity observed in plants (Zawoznik et al, 2007;Zhang and Chen, 2011). Previous studies have shown that SA treatment mitigates the oxidative stress generated by Cd in different plant species such as barley (Metwally et al, 2003), soybean (Drazic and Mihailovic, 2005), rice (Guo et al, 2007), maize (Krantev et al, 2008), pea (Popova et al, 2009), and hemp (Shi et al, 2009). However, little has been reported about the role of SA in the increase of total antioxidant capacities under Cd stress.…”
mentioning
confidence: 99%
“…Signaling compounds such as SA or NO have dual functions as potent oxidant or effective antioxidant mostly depends on their concentrations and on the status of the environments (Shi et al 2009). When applied at appropriate low concentrations, they are able to reduce the severity of stresses in many species (Horvath et al 2007), by inducing transient oxidative stress in plants, which acts as a hardening process, increasing antioxidant capacity of plants (Horvath et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SA is an important signal involved in the activation of plant defense responses against abiotic and biotic stresses and plays a crucial role for the regulation of physiological and biochemical processes (Saruhan et al 2012). Effects of SA on plants are concentration dependent, treatment duration, plant species, age at treatment, and plant organ examined used for pretreatment (Shi et al 2009).…”
Section: Introductionmentioning
confidence: 99%